Postpandemic potential: Readying for the new era of international student enrollment - Rickert, Alex (Journal of International Students, 2025)
The COVID-19 pandemic disrupted global student mobility, leading to sharp declines in international student enrollment at U.S. higher education institutions (HEIs). Research on the pandemic’s effects highlights key challenges faced by international students, including financial instability, mental health concerns, and experiences of racism and xenophobia. Institutional responses varied, with some universities leveraging distance technology and policy adaptations, while others failed to provide adequate support. As mobility restrictions ease, international enrollment is rebounding, presenting HEIs with new opportunities to engage and attract students. Using Push-Pull Theory as a framework, this study examines how HEIs can strengthen pull factors—such as reaffirming the value of international students, expanding recruitment into new markets, and enhancing institutional infrastructure to support students during global crises. By understanding the lessons learned from COVID-19 and preparing for future disruptions, U.S. HEIs can position themselves competitively in an evolving global education landscape.